FIRING BEHAVIOUR OF CERAMIC WHITEWARE BODIES INCORPORATED WITH LOCAL FELDSPATHIC SOURCES (Jurnal Teknologi (Sciences & Engineering), 2016)
Quarry dust is a by-product of granite quarrying activities. Granite fragments, that are normally obtained from blasting granite rocks in a particular quarry, are subjected to a number of machineries of decreasing crushing aperture sizes and each attendant sieving to obtain granite aggregates of the desired size, normally 20 mm, 10 mm, etc. Â These are to be used in the construction of buildings as coarse aggregates in concrete mixes, as well as in the laying of tarred roads. The finest fraction, nominally below 7 mm or 5 mm in size depending on the practice of the quarrying company, is normally dumped on site. It is considered to be a waste that needs to be disposed of. Apart from attending to the environmental issue, the reuse of such waste material in the development of new products would be an attractive commercial proposition. In this work, granite quarry dust was incorporated into a clay-based ceramic body to replace the use of feldspar (an expensive component) as the fluxing agent in such triaxial clay whiteware compositions. A fluxing agent is the component in a ceramic body composition that melts first and functions as the component that binds together all the other solid particles into a rigid body. Initially, the quarry dust was chemically and mineralogically characterized before mixing with clay at a fixed 45:55 weight ratio. The mixtures were then pressed and fired at various temperatures before testing the properties of the fired products. A comparison was made with a local feldspathic source from Gua Musang to ascertain the feasibility of such replacement to produce high quality ceramic bodies. It was found that mineralogically the granite quarry dust consists of K-feldspar (or orthoclase) as compared to Na-feldspar (or albite) found in the Gua Musang feldspar. This led to melting at a lower temperature of the former but exhibited a much more viscous melt. At the same time, the higher iron content in the granite quarry dust led to a much darker colourisation of the body upon firing. In conclusion, the granite quarry dust has been found to be successful in lowering the maturing temperature of ceramic bodies compared to the Gua Musang feldspar beside conferring stability of the low porosity property over a wider firing temperature.Â